EDUPRENEURSHIP-BASED COMMUNITY EMPOWERMENT THROUGH CUCUMBER FOOD CREATIONS - Billy Hari Pamungkas; Muhammad Faisal Najmudin; Nafiza Izzarulloh; Purnomo Purnomo (IKIP Siliwangi Bandung, 2022)
This study discusses